Russianisms and Ukrainisms in the Czech language in the late 20th and early 21st centuries: New connotations, contextual and pragmatic meanings - Viktorovich Savchenko, Aleksandr (Slavia Centralis, 2021)
The use of the method of so called lexical transplantation, i.e. the inclusion to the text (written or oral) foreign lexical units in the original or transformed form (phonetic, morphological, lexical assimilation in the host language) is a very characteristic and specific feature of modern discourse. The article is devoted to the history of the borrowings, including the cases of so-called lexical transplantation, i.e. inclusion (resp. usage) to the text (written or oral) foreign words and expressions from another language in their original or slightly modified form, in our case from the closely related languages Russian and Ukrainian to Czech: their meaning, usage and pragmatic functions in the language. In the article are presented examples of usage of "transplantants-Russianisms and Ukrainisms" in the Czech language, described their typology and basic functions.